Management of patients with atopic dermatitis during pregnancy - E. A. Orlova; O. P. Vinogradova; E. M. Kostina; Yu. A. Kandrashkina (Лечащий Врач)
The problem of the peculiarities of the course of allergic diseases during pregnancy, as well as rational and safe approaches to their treatment, is in the focus of close attention of specialists. The article presents the clinical and pathogenetic characteristics of atopic dermatitis in pregnant women. Attention is paid to the principles of diagnosis of atopic dermatitis during pregnancy. Early diagnosis is especially important when pregnancy occurs, since children born to a family where both parents have atopy have a 75% risk of developing atopic dermatitis. First of all, for the prevention of possible exacerbations of atopic dermatitis in pregnant women, it is necessary to resolve the issue of eliminating trigger factors and exclude contact with allergens, special attention should be paid to a hypoallergenic diet. The issues of the choice of tactics of management and therapy of dermatosis are considered, taking into account clinical studies, assessment of the degree of risk for the pregnant woman and the fetus. The features of the use of emollients, topical glucocorticosteroids, topical antipruritic agents, sedatives and antihistamines as part of the complex therapy of pregnant women with atopic dermatitis are discussed.